Evaluation of the World Health Organization outcome standards at the early and late post-operative visits following cataract surgery - Meyer, Jay J; Murray, Neil L (Nepalese Journal of Ophthalmology, 2020)
Introduction: This study was conducted to determine whether the World Health Organization (WHO) visual acuity standards are correlated between the early and late early post-operative periods following phacoemulsification (phaco) and small incision extracapsular cataract surgery (SICS). Secondary aims were to compare visual outcomes and complications following SICS and phaco.Methods: Retrospective cohort study following phaco and SICS performed by one surgeon. Primary outcome measures included uncorrected visual acuity (UCVA) and best corrected visual acuity (BCVA) at the early (≤72 hours) and late (≥21 days) post-operative visits. Secondary outcome measures included complications and astigmatism.Results: 705 eyes were studied (509 phaco, 196 SICS). The correlation for UCVA between early and late follow-up examinations was higher for phaco (rs=0.58) compared to SICS (rs=0.45, p=0.04) while correlation for BCVA was similar (phaco,rs=0.52; SICS, rs=0.47; p=0.44). At the early post-operative visit, a higher proportion in the phaco group achieved ≥6/18 UCVA (81.5% phaco vs 64.8% SICS, p